The Effect of Ascorbic Acid on Salt Tolerance and Seedling Performance in Triticum durum Defs. ‘Douma 3’ Under Salinity Stress in Syria - Nour Ali; Anikó Nyéki; Aïda Jalloul; Tarek Alahmad (Agronomy, 2024)
This study was conducted to evaluate the laboratory tolerance of the durum wheat cultivar (Douma 3) when treated with two levels of ascorbic acid (5 ppm and 10 ppm, in addition to a control treatment soaked in water) under two levels of salt stress (50 mM and 100 mM NaCl, in addition to a control). The experiment took place at the Field Crops Department labs, Faculty of Agricultural Engineering, University of Damascus, during the 2022–2023 agricultural season. The aim was to study the effect of ascorbic acid on seed reserve utilization efficiency, peroxidase enzyme activity, and its role in salt stress tolerance. The experiment followed a randomized complete block design (RCBD) using factorial ANOVA with two replicates. The results showed significant differences between the treatments, with the priming of seeds soaked in a 5 ppm ascorbic acid solution (A1) significantly outperforming in terms of seedling dry weight (22.67 mg/seedling), remaining seed dry weight (7.5 mg/seed), seed reserve utilization efficiency (0.47 mg/mg), and salt tolerance index (89.80%). Simple correlation analysis showed a significant positive correlation between seedling dry weight (SDW), seed reserve utilization efficiency (SRUE) (0.881), and salt tolerance index (STI) (0.746 *). However, a negative and non-significant relationship was observed between the remaining seed dry weight (RSDW) and other traits. Moreover, SRUE had a significant positive correlation with STI (0.814). Both total soluble protein concentrations and peroxidase enzyme activity increased under salt stress conditions following pre-treatment with ascorbic acid compared to the control. The highest protein concentration and peroxidase enzyme activity were observed with the 5 ppm ascorbic acid treatment (A1).